Time-Dependent Periimplant Bone Reaction of Acidic Monomer-Treated Injection Molded Zirconia Implants in Rabbit Tibiae. Issue 3 (June 2015) - Shon, Won-Jun; Woo, Kyung Mi; Kim, Hong-Kyun; Kwon, Ho Beom; Shin, Seung-Yun; Park, Young-Seok
<x xml:space="preserve">Abstract</x> Purpose: The aim of this study was to evaluate and compare the osseointegration of zirconia implants in rabbit tibiae with and without 10-methacryloyloxydecyl dihydrogen phosphate (MDP) treatment. Materials and Methods: Twenty-eight rabbits received a total of 112 external hex-type implants made by the powder injection molding technique with and without MDP treatment before installation in the tibiae. The contact angles on the zirconia implants and zirconia discs before and after MDP application were evaluated. Removal torque (RT) and bone-implant contact (BIC) ratios were measured. Results: The MDP treatment markedly enhanced the hydrophilicity and seemed to alter the topography and chemical composition of the implant and disc surface. As the healing time increases, the BIC and RT were increased in both groups. The MDP-treated implants exhibited higher BIC values than the control implants after 2 and 4 weeks of healing. The RT was higher in MDP-treated implants after 2 weeks of healing but not after 4 weeks of healing. Conclusion: The 10-MDP treatments made the surface more hydrophilic and enhanced the osseointegration of the implants in the early healing phase.